Goliath - Onyebuchi, Tochi (Tordotcom, 2022)
"In the 2050s, Earth has begun to empty. Those with the means and the privilege have departed the great cities of the United States for the more comfortable confines of space colonies. Those left behind salvage what they can from the collapsing infrastructure. As they eke out an existence, their neighborhoods are being cannibalized. Brick by brick, their houses are sent to the colonies, what was once a home now a quaint reminder for the colonists of the world that they wrecked. A primal biblical epic flung into the future, Goliath weaves together disparate narratives-a space-dweller looking at New Haven, Connecticut as a chance to reconnect with his spiraling lover; a group of laborers attempting to renew the promises of Earth's crumbling cities; a journalist attempting to capture the violence of the streets; a marshal trying to solve a kidnapping-into a richly urgent mosaic about race, class, gentrification, and who is allowed to be the hero of any history"--